Role Budget Participation and Budget Slack on Supply Chain Operational Performance: Evidence from Indonesian Textile Industry - Yusro Hakimah; Andhyka Tyaz Nugraha; Hadiati Fitri; Christianus Manihuruk; Masnilam Hasibuan (International Journal of Supply Chain Management, 2019)
Budgets are instruments that managers can use to help them in completing their business activities. Now various countries are focusing budget participation to boost supply chain activities. Objective of the current study is to examine the role of budget participation in supply chain operational performance among Indonesia textile industry. Moreover, moderating role of management control system was also examined. Interactive control system and boundary control system taken as moderating variable. For this purpose, data were gathered from textile companies of Indonesia. Employees of these companies were selected as respondents. Total 500 questionnaires were distributed to collect the data. Partial Least Square (PLS) were utilized as statistical tool to analyse the data. Results shows that budget participation increases the supply chain operational performance. Moreover, management control system also has significant role in supply chain operational performance.